Proceedings of the workshop on information technology tools for natural disaster risk management, February 04-06, 1998, AIT, Thailand - Information Technology Tools for Natural Disaster Risk Management Thailand) (1998; Herath, Srikantha; International Center for Disaster-Mitigation Engineering (INCEDE); United Nations University (UNU); Asian Center for Research on Remote Sensng (ACRoRS) (Tokyo, Japan International Center for Disaster-Mitigation Engineering, Institute of Industrial Science, University of Tokyo, 1999)
"Information Technology Tools for Natural Disaster Risk Management" is a timely compilation of selected reviewed papers presented at the international workshop held under the same title in Asian Institute of Technology, Bangkok, Thailand in 1998. The workshop brought together researchers, engineers, and scientists working with information technology tools ranging from GIS, remote sensing, communication networks and database applications for natural disaster risk reduction to exchange ideas and experiences. The volume details applications in floods, earthquakes, risk assessment, disaster monitoring and response, data management and role of information technologies in disaster management focusing on Asia Pacific Region. It also provides a host of information on the vast range of possibilities available for natural disaster risk management in emerging technologies.
Earth observation in multi-media age by Shunji Murai -- Development of a GIS-based framework for ground motion analysis by Tso-Chien Pan and Chit Boon Koh -- Use of GIS for 3D soil modelling and applications to seismic hazard assessment by Carlos Villacis and Laura Dwelley -- Application of IT in natural disaster risk management : case study of Bandung earthquake mitigation project by Krishna S. Pribadi, H. R. Pertiwi and I. Sjabri -- Use of ANN for seismic risk assessment by S. Mourya and T. K. Datta -- Earthquake database and seismic zoning of Bangladesh by MD. Hossain Ali -- Seismicity in Bangladesh and assessment of existing earthquake catalogue by Mehedi Ahmed Ansary -- Development of a database of projects related to pollution hazards on the natural environment by N. T. Sohan Wijesekera and P. M. Gunasekera -- Methodology for flood damage assessment using GIS and distributed hydrologic model by Dushmanta Dutta and Srikantha Herath -- The implementation of GIS technology in urban flood dynamic simulation model by He-Ping Hu, Shen Yi and Weng Wenbin -- Channel changes using satellite data for flood mitigation - Nepal case study on watershed degradation and flood plain monitoring by Lal Samarakoon, Kiyoshi Honda and Akichika Ishibashi -- Use of NOAA/AVHRR data for flood disaster monitoring in Mekong River Delta by Hoang Minh Hien -- Flood damage real-time estimation model based on remote sensing and GIS by Xiuwan Chen -- Lahar damage assessment using satellite remote sensing : The Mount Pinatubo experience by Epifanio D. Lopez, Randy John N. Vinluan and Enrico C. Paringit -- Flood control management - Towards and environment friendly approach by MD. Mafizur Rahman, N. Tamai and Y. Kawahara -- Preparation of spatial data sets for physically based hydrologica models by Srikantha Herath, Ragunath Jha, Dawen Yang and Dushmanta Dutta -- Problems and solutions of thermal infrared remote sensing for drought-monitoring by Xiaowen Li and Alan H. Strahler -- Topographic measurement for volcanic mountain using SAR interferometry by Mitsuharu Tokunaga -- Development of a GIS-based decision support system for Indian cities affected by Cyclones by K. V. Adityam and Debashish Sarkar -- Developing decision support systems for mitigating natural hazards risks through relocation by Ali Asgary -- Classification of urban areas by characteristics of power load curves by Kimiro Meguro, Michiyo Soejima, Fumio Yamazaki and Tsuneo Katayama -- Geoinformatic data base and space technology for natural disaster management in India by R. B. Singh -- GIS for efficient natural disaster preparedness and mitigation in Sri Lanka by S. B. Weerakoon -- Monitoring network for earthquake risk management by Douglas Ling -- Disasters, economic development and the utilization of information technologies by Ino Rossi -- Internet agent and the natural disaster risk management by Frank Chang -- Databse centered simulation using WWW by Srikantha Herath and Assela Pathirana -- Development of an on-line GIS for a network environment : possible applications in hazard ris management and environmental monitoring by Venkatesh Raghavan, Shinji Masumoto, Mamoru Shibayama and Kiyoji Shiono
Organized by International Center for Disaster-Mitigation Engineering (INCEDE), United Nations University (UNU), Asian Center for Research on Remote Sensing (ACRoRS)
Fi-13443g -- Donated by Dr. Leonardo Q. Liongson, Professor, Institute of Civil Engineering, UP Diliman.
Keywords: Emergency management -- Technological innovations; Emergency management -- International cooperation; Emergency management -- Case studies